Heat Flow Distribution in the Chukchi Borderland and Surrounding Regions, Arctic Ocean - T. Zhang; Z. Y. Shen; F. Zhang; M. Ding (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Fifty new heat flow measurements from the Chukchi Borderland (CBL) and adjacent regions of the central Arctic Ocean are reported, where heat flow measurements have been very limited. The average heat flow of the CBL (65 mW/m2) is significantly higher than that of the entire Amerasia Basin (53 mW/m2). In the CBL, the heat flow of the Chukchi Plateau (CP), Northwind Basin (NWB), and Northwind Ridge (NWR) are 64 mW/m2, 69 mW/m2, and 60 mW/m2, respectively. With the aid of nearby seismic profiles, the elevated regional heat flow in the CP and NWR was attributed to the enhanced radiogenic heating of the thick crust (25–29 km), while the most prominent heat flow in the relatively thin crust of the NWB is likely due to the residual heat of a major tectonic extension event. Further numerical heat conduction modeling suggests that the initial rifting of the Amerasia Basin during the Jurassic–Early Cretaceous could not induce such high heat flow in the NWB. Together with recent interpretations of seismic profiles, the elevated heat flow in the NWB could be explained by the residual heat of the Late Cretaceous–early Cenozoic extension. This extension event was contemporaneous with the seafloor spreading in the Makarov Basin and had also been associated with the onset of seafloor spreading in the Eurasia Basin.